2012
DOI: 10.1007/s10936-012-9207-5
|View full text |Cite
|
Sign up to set email alerts
|

Determiner Primes as Facilitators of Lexical Retrieval in English

Abstract: Gender priming studies have demonstrated facilitation of noun production following pre-activation of a target noun's grammatical gender. Findings provide support for models in which syntactic information relating to words is stored within the lexicon and activated during lexical retrieval. Priming effects are observed in the context of determiner plus noun phrase production. Few studies demonstrate gender priming effects in bare noun production (i.e., nouns in isolation). We investigated the effects of English… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Cubelli et al (2005) found gender interference for bare nouns in Italian, Akhutina et al (2001) found gender priming effects in Russian, and Paolieri et al (2011) found gender interference in naming bare nouns in Italian. Finally, in English, Gregory et al (2012) primed production of mass and count nouns with congruent determiners. So, across a range of languages, there is evidence of activation of syntactic information, even when this is not explicitly required for the production task, lending support to the claim that syntax is represented lexically.…”
Section: Theories Of Spoken Word Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cubelli et al (2005) found gender interference for bare nouns in Italian, Akhutina et al (2001) found gender priming effects in Russian, and Paolieri et al (2011) found gender interference in naming bare nouns in Italian. Finally, in English, Gregory et al (2012) primed production of mass and count nouns with congruent determiners. So, across a range of languages, there is evidence of activation of syntactic information, even when this is not explicitly required for the production task, lending support to the claim that syntax is represented lexically.…”
Section: Theories Of Spoken Word Productionmentioning
confidence: 99%
“…Count nouns such as cat frequently occur with determiners such as 'a', whereas mass nouns such as milk frequently occur with determiners such as 'some'. A few studies have capitalized upon this difference to investigate noun syntax in English (Gregory et al, 2012;Herbert and Best, 2005;Herbert and Best, 2010;Vigliocco et al, 1999).…”
Section: Mass and Count Nounsmentioning
confidence: 99%